Unusual Formal 1,2-Addition of Pyrazolones to 3-Indolylmethanols: Regiospecific Synthesis of 2,3-Disubstituted Indoles - Liu, Yan; Zhu, Ren-Yi; Li, Han-Zhu; Jiang, Yan; Shi, Feng (Synthesis, 2015)
An unusual formal 1,2-addition reaction of pyrazol-5-ones with isatin-derived 3-indolylmethanols has been established, which is suggested to proceed via a cascade reaction sequence of oxa-Michael addition, [3,3] rearrangement, 1,3-H shift and tautomerization. During the proposed reaction pathway, [3,3]-sigmatropic rearrangement of the oxa-Michael addition product is thought to be the key step leading to the regiospecific formal 1,2-addition reaction. This approach not only provides an easy access to 2,3-disubstituted indoles, but also has realized the rarely reported formal 1,2-addition of 3-indolylmethanols with regiospecificity, which opens a new window for investigations on 3-indolylmethanol-involved transformations.
Keywords: regioselectivity; rearrangement; tandem reaction; indoles; phosphoric acids